PENGARUH INDEPENDENSI, DISKRIMINASI GENDER, PENGALAMAN, PENDIDIKAN, KECERDASAN EMOSIONAL, DAN KECERDASAN SPIRITUAL TERHADAP PROFESIONALISME AUDITOR (Studi Empiris Pada Auditor di Kantor Akuntan Publik di Pekanbaru) - Simatupang, Abram Heldon; Savitri, Enni; Rofika, Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the affect of independency, gender discrimination, experience, education, emotional intelligence, and spiritual intelligence on auditor professionalism, especially those who are working in Public Accountant Firms of Pekanbaru.The population of study is auditors who worked on the Public Accountant Firms of Pekanbaru .The sample is 50 auditors who worked in 7 Public Accountant Firms of Pekanbaru. Methods of data collection in this study is the method of questionnaire survey using instruments that are delivered directly to the Public Accountant Firms of Pekanbaru. Methods of Analysis is conducted with a multiple regression analysis using SPSS (Statistical Product and Service Solutions )Version 21.The results of testing that has been done.Partial regression test (t test) showed that the auditors’ independency, experience, emotional intelligence, and spiritual intelligence had a influences significantly and positively towards auditor professionalism, while gender discrimination and auditor’s education have no effect significantly on their professionalism. The coefficient of determination in this study was 71,5 % .These four variables affect the dependent variable was 71,5 % , while 28,5 % is influenced by other variables that are not addressed in this study .Keyword : independency, gender discrimination, experience, education, emotional intelligence, spiritual intelligence, and professionalism